KARAKTERISTIK IBU BERSALIN DENGAN PARTUS LAMA DI RSUD PURBALINGGA PERIODE 2007-2009 - Fauziah Hanum Nur Adriyani; Sriyanti Sriyanti (Universitas Harapan Bangsa Purwokerto, 2011)
Based on pre-survey studies the incidence of prolonged labor obtained from PurbalinggaHospital Medical Record in 2007 a number of 85 cases (4.5%) out of 1888 births, in 2008some 85 cases (7.92%) out of 1,073 births, while in 2009 there were 121 cases (8.24%) out of1,469 births. (Purbalingga Hospital Medical Record Data, 2007-2009). Interest to describematernal characteristics with prolonged labor in hospitals Purbalingga 2007-2009 period.This research was conducted by using quantitative descriptive method with retrospectiveapproach, the population is all the mothers who have prolonged labor incidence in hospitalsPurbalingga the period 2007- 2009 as many as 291 cases. This study uses secondary datatypes. Results maternal characteristics with prolonged labor in hospitals Purbalingga 20072009 period, it is known that the normal delivery of the 291 respondents are respondentsaged between 20 and 35 years have at most that number of 114 respondents (39.2%) andmost of the 211 respondents multiparas (72.5%), prolonged labor incidence of maternalexperienced by respondents aged 20-35 years and multiparous.Keyword :Characteristics, maternity, prolonged labor